After the Fall : War and Occupation in Irène Némirovsky's Suite française - Bracher, Nathan, 1953- (Book collections on Project MUSE., 2010)
Irene Nemirovsky's war narrative, Suite franc̦aise, was discovered and published posthumously in 2004, more than sixty years after it was written. A Jewish Russian immigrant who had achieved literary stardom during the twenty years she lived in France, Nemirovsky wrote her novel during the first years of the Occupation, before she was deported by the Nazis to Auschwitz, where she died in 1942. When published, the book produced an immediate international sensation and has since been translated into more than twenty-five languages. While giving rise to a certain amount of controversy, the novel has been widely acclaimed as a literary masterpiece providing a devastating portrayal of France's defeat and occupation. In this work, the first critical monograph on Suite franc̦aise, Nathan Bracher shows how, first amid the chaos and panic of the May-June 1940 debacle, and then within the unsettling new order of the German occupation, Nemirovsky's novel casts a particularly revealing light on the behavior and attitudes of the French as well as on the highly problematic interaction of France's social classes. It offers valuable insights on a number of subjects (in particular, the civilian exodus, the relations of French women with German soldiers, and socio-economic conflicts under the Occupation) that, until now, have been too often neglected or misunderstood, while at the same time displaying a striking originality when compared to other discourses and narratives dating from the same period. Bracher dispels a number of misconceptions that have arisen when Suite franc̦aise has been assessed on the basis of biographical presumptions or with respect to current imperatives of the "duty to remember." Instead of viewing Suite franc̦aise as a source of information about the author or as a simple instrument of memory, we can best understand the novel, Bracher argues, as a specifically configured literary text whose voice can engage its readers in a critical dialogue with the dramatic era of the catastrophic fall of France and the ensuing Occupation. Contrary to certain polemical interpretations, Bracher shows that Nemirovsky's searing novel not only makes a mockery of Vichy ideology but even adumbrates an ethic of resistance